Systematic Literatur Review : Pengaruh Pendapatan Asli Daerah dan Belanja Modal Terhadap Kinerja Keuangan Pemerintah Daerah - Nawang Wulan Cahya Ningrum; Putri Silviana; Dien Noviany Rahmatika (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to investigate how the financial achievements of Indonesian regional authorities are influenced by capital expenditure and PAD. The study employs the Systematic Literature Review (SLR) methodology. This method is used to ascertain, research, assess, and interpret any surviving studies relating to interesting phenomena using specific relevant research problems. SLRs can be used to find journals and conduct thorough reviews, each procedure adhering to standards or guidelines. In this study, 50 journals were used as references. The study's findings indicate Research findings prove that pure regional revenues provide important benefits regarding regional financial performance. This demonstrates how raising local real income can improve local governments' financial performance in satisfying development and community demands. On the other side, capital spending also significantly improves local governments' financial performance. This means that a rise in capital spending can strengthen the regional development structure and increase the competitiveness of the local economy. This research provides policy implications that “municipal authorities must focus on